Fairy Cups TM a business proposal for small scale production of cupcakes - Perez, Louise Melody N. (2010)
The study is a feasibility for a food business, a cupcake business named Fairy Cups TM and will offer a wide variety of cupcake that will enable your mind to remember the certain craving for such cupcake.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Cupcake